Removal of Methylene Blue Dye using Carbon Derived from Bulb of Zephyranthes citrina: Adsorption and Kinetic Studies - Prakash, J.; Vedanayaki, S.; Karthick, K. (Asian Journal of Chemistry, 2020)
The studies open up an innovative approach and investigate porous, efficient raw carbon from Zephyranthes citrina bulb, which was used as an adsorbent to remove organic dyes. The well-dried and finely powdered Zephyranthes citrina bulb was carbonized at 900 ºC. The carbonized crude Z. citrina sample was characterized by FT-IR, UV-visible, scanning electron microscopy (SEM), BET, X-ray diffraction (XRD) techniques and their adsorption potential to remove the basic methylene blue dye from an aqueous sample. Adsorption studies comprise both adsorption isotherm and kinetic methods. The processes were carried out with diverse adsorbate concentrations and adsorbent quantities at various time intervals in the batch process. Kinetic models of Lagergren first order, pseudo-second order and intra particle diffusion were used to assess the kinetics and adsorption mechanism. The results revealed that the adsorption process follows the first order kinetic model of Lagergren. The BET isotherm model confirmed that it has an excellent adsorption capacity in an adsorption process. Based on the results obtained, the maximum removal (81%) of dye was achieved in a solution containing 50 mg of 50 mL dye at 3 h for methylene blue. The results indicated that the bulb of Zephyranthes citrina carbon is a proficient adsorption material and is also used as a cost effective alternative that can adsorb dye from an aqueous solution without activation treatment.